Role of Dermal Fillers in Aesthetic Dentistry - Kayal Vennila Mahendran1 , Jayalakshmi Somasundaram2, Vinay Sivaswamy3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Dermal fillers are gel like substances which are injected beneath the skin.It is also used to soften creasesand enhance facial contour. The potential promise of the role of dermal fillers in Aesthetic dentistry involvesimportant clinic uses. Dermal fillers are an important tool in the armamentarium of an aesthetic surgeon inthe management of ageing skin. A surge within the use of fillers has been witnessed thanks to increasingawareness among people, easy availability of fillers and increased enthusiasm amongst the dermatologistsand plastic surgeons to use this modality. In this era of evidence-based medicine and litigations againstdoctors, Oral Surgeons should be vigilant about different acts of omission and commission in the use offillers.Dermal fillers have revolutionized the sector of cosmetic dermatology, as evidenced by the presenceof an outsized number of products within the market. Even though fillers have been classified as a cosmeticdevice and have been FDA approved only for wrinkle management, they have been used for several otheraesthetic and non-aesthetic indications too. This article briefly discusses the dos and don’ts with referenceto dermal fillers.The review is done to fulfill the need to evaluate prevailing awareness regarding theapplication of dermal fillers in dentistry. Further, the review aims to establish the differences between fillerinjections in a dental procedure. The review also aims to consolidate recent advances in dermal fillers andits subsequent role in cosmetic dentistry.Search engines like NCBI- pubmed,mesh, google scholar wereused to review articles since the year 2000 which were consolidated and analysed. The review provided anextensive outlook regarding the popularity ,extent of use ,demand and its advanced administrative techniquesin aesthetic dentistry .